The Study and Analysis of Roles of Wisdom in Arts and Crafts for Cultural Performances in Chiang Mai - Hongyeesibed, Sariya (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2022)
This research article was aimed to study and gather knowledge and wisdom on arts for cultural performances in Chiang Mai in order to analyze the roles and responsibilities of local arts and craftmanship towards the society. A qualitative research methodology to collect data from academic documents observations interviews and media analysis were conducted to create knowledge that can be integrated and utilized in managing cultural information in Chiang Mai. The results showed that arts and crafts are strongly inspired by the locality of Lanna culture traditions traditions and beliefs through physical appearance of the local handicrafts. The research revealed that the arts and crafts of the villagers in 25 districts of Chiang Mai Province consisted of 51 items can be divided into 6 groups including woven handicrafts wood carving craft basketry handicrafts pottery handicrafts silver and metal handicrafts and Mulberry paper handicrafts. In each group there were products used in daily life and decorative ornaments that were unique and diverse in each locality reflecting the roles and responsibilities of arts and crafts that affect society in various contexts: 1) wisdom as a tool to transfer and reflect community wisdom allowing viewers to entertain and appreciate the local culture that is the root of the people in the community 2) education being an important part in inserting content in various courses for future generations to preserve and distribute 3) business can generate income for the community and other related parties and 4) tourism cultural heritage in public relations for tourism.